2006
DOI: 10.1002/pon.1105
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned in the implementation of an innovative consultation and liaison service for children of cancer patients in various hospital settings

Abstract: Hospital-based services for cancer patients with children under the age of 18 should carefully address patients' fears of psychiatric stigmatization. Furthermore, they should include modules for acute crisis intervention. Implications for future implementation activities in this field are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 34 publications
3
27
1
5
Order By: Relevance
“…This intervention confirms the previous studies about the importance of an open communication to support children to face with cancer's diagnosis [5,10,[14][15][16]. The project highlights the advantages of direct engagement of children in the communication of the parent's illness to improve the relationships within the family.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This intervention confirms the previous studies about the importance of an open communication to support children to face with cancer's diagnosis [5,10,[14][15][16]. The project highlights the advantages of direct engagement of children in the communication of the parent's illness to improve the relationships within the family.…”
Section: Discussionsupporting
confidence: 74%
“…They told their parents and clinicians that they were satisfied with their direct engagement, without parents present, with the specialists because in this way they felt they were an important part of the family system and they understood that in their families no lies were being told about the illness and so they could trust their parents. Some studies underline that communication and expressiveness in families can be identified as a key issue in children's positive coping with parental illness [10,13]. Our findings in fact underlined the absence of psychological problems in children after the intervention.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Nicholls et al (17) identifies that the most unmet needs for these children are during the initial diagnostic stage and is complemented by another study (33) that shows parental stressors, and thereby stressors on these children, also decrease with time, suggesting that an early approach would be more beneficial. However, Romer et al implemented an early curriculumbased intervention and concluded that these parents and their children are overwhelmed early and need time to adjust, cope, and establish a relationship with the medical staff for the intervention to be effective, suggesting a 3 month later approach as more beneficial (34).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, despite the finding that existing guidelines for psychosocial cancer care include the families and children of cancer patients, 9 the integration of family-centered support into oncology care is not systematic. 29 In addition, patients might prefer brief child-focused and familyfocused interventions within the context of routine care. The step of seeking specific family-centered service exclusively might be too far.…”
Section: Discussionmentioning
confidence: 99%